2016
DOI: 10.1002/cssc.201601234
|View full text |Cite|
|
Sign up to set email alerts
|

The Quest for Value‐Added Products from Carbon Dioxide and Water in a Dielectric Barrier Discharge: A Chemical Kinetics Study

Abstract: Recycling of carbon dioxide by its conversion into value-added products has gained significant interest owing to the role it can play for use in an anthropogenic carbon cycle. The combined conversion with H O could even mimic the natural photosynthesis process. An interesting gas conversion technique currently being considered in the field of CO conversion is plasma technology. To investigate whether it is also promising for this combined conversion, we performed a series of experiments and developed a chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 89 publications
(247 reference statements)
12
105
1
Order By: Relevance
“…Indeed, recent modelling studies of CH 4 /O 2 mixtures have indicated a preferential formation of H 2 O from OH radicals [50]. These H 2 O molecules will promote the back reaction of CO into CO 2 , as suggested based on CO 2 /H 2 O models [56]. This can explain the lower CO 2 conversion in DRM for a BaTiO 3 packing, compared to pure CO 2 splitting.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, recent modelling studies of CH 4 /O 2 mixtures have indicated a preferential formation of H 2 O from OH radicals [50]. These H 2 O molecules will promote the back reaction of CO into CO 2 , as suggested based on CO 2 /H 2 O models [56]. This can explain the lower CO 2 conversion in DRM for a BaTiO 3 packing, compared to pure CO 2 splitting.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, this reaction did not contributet oC O 2 conversion at 5% CH 4 in the mixture and waso nly importanta tl arger CH 4 fractions, as is clear from Figure 7. This reverse reactionw as also the limiting factor in CO 2 conversion in aD BD operating in a CO 2 /H 2 Om ixture, [90] and was even more important at higher H 2 Of ractionsi nt he mixture, which explainsw hy the addition of H 2 Or esulted in ad rop in the CO 2 conversion. [90] Thes itua-tion was ab it different in our case because at higherC H 4 fractions, the Ha toms formed upon dissociation of CH 4 played a more importantr ole in the CO 2 conversion, that is, the forward (loss) reactionu pon collision with Ha toms was more important than the reversereaction (production of CO 2 ).…”
Section: Calculated Species Densities Inside the Plasmamentioning
confidence: 93%
“…In recent years, several plasma chemistry models were presented in literature, for CO 2 splitting, CH 4 reforming, CO 2 /CH 4 , CH 4 /O 2 , CO 2 /H 2 O, CO 2 /H 2 , as well as CO 2 /N 2 or CH 4 /N 2 mixtures, because N 2 is one of the most important components in gas effluents. Note, however, that not all these studies were devoted to gas conversion applications.…”
Section: Introductionmentioning
confidence: 99%